2017
DOI: 10.1051/0004-6361/201629924
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of photospheric magnetic elements corresponding to coronal features to understand the EUV and UV irradiance variability

Abstract: Context. The magnetic field plays a dominant role in the solar irradiance variability. Determining the contribution of various magnetic features to this variability is important in the context of heliospheric studies and Sun-Earth connection. Aims. We studied the solar irradiance variability and its association with the underlying magnetic field for a period of five years (January 2011-January 2016). We used observations from the Large Yield Radiometer (LYRA), the Sun Watcher with Active Pixel System detector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…Using our algorithm we have separated out the XBPs component from the quiet Sun areas, since quiet Sun is the combination of both background regions (BGs) and XBPs. In the case of EUV and UV image segmentation in our previous studies (Kumara et al, 2014;Zender et al, 2017) we did not separated out the bright points from the quiet Sun component, hence we had to deal with variations of the whole quiet Sun regions. In the present study, we have identified, (separated out background regions and XBPs), and extracted automatically the total number of XBPs based on their intensity levels, morphological structures and sizes (compared to other large scale features like ARs and masking them) over the full-disk images observed in Al_mesh), all this on a daily basis for the period of 13 years (February 2007-March 2020, which covers Solar Cycle 24).…”
Section: Number Variation Of Xbps With the Solar Magnetic Activity Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Using our algorithm we have separated out the XBPs component from the quiet Sun areas, since quiet Sun is the combination of both background regions (BGs) and XBPs. In the case of EUV and UV image segmentation in our previous studies (Kumara et al, 2014;Zender et al, 2017) we did not separated out the bright points from the quiet Sun component, hence we had to deal with variations of the whole quiet Sun regions. In the present study, we have identified, (separated out background regions and XBPs), and extracted automatically the total number of XBPs based on their intensity levels, morphological structures and sizes (compared to other large scale features like ARs and masking them) over the full-disk images observed in Al_mesh), all this on a daily basis for the period of 13 years (February 2007-March 2020, which covers Solar Cycle 24).…”
Section: Number Variation Of Xbps With the Solar Magnetic Activity Cyclementioning
confidence: 99%
“…The long-term irradiance variations are due to the changing emission of bright magnetic elements e.g. (Foukal and Lean, 1988;Kariyappa and Pap, 1996;Worden, White, and Woods, 1998;Kariyappa, 2000Kariyappa, , 2008bVeselovsky et al, 2001;Kumara et al, 2012Kumara et al, , 2014Zender et al, 2017), and the short-term irradiance variations are directly related to active regions as they evolve, fragment, and move across the solar disk (Lean, 1987;Giono et al, 2021;van der Zwaard et al, 2021). The reason for the difference between the observed and modeled solar irradiance variability and the underlying physical mechanisms of solar irradiance variability are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A segmentation of solar features into active regions (ARs), coronal holes (CHs), and the quiet Sun (QS), and its application to EUV solar disk images has been presented by Kumara et al (2014) and been extended by Zender et al (2017) to the underlying magnetograms from SDO/HMI. These earlier publications of this study are referenced in the following as Paper I and Paper II, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…One of the recent techniques that can track the flux of magnetic features from magnetograms and determines both emergence and cancellation of the magnetic structures is the magnetic ball-tracking algorithm (Attie & Innes 2015). Zender et al (2017) introduced a segmentation method by thresholding on jointing adjacent pixels in a magnetogram. Pérez-Suárez et al (2011) gave a comprehensive review of the automatic detection of solar magnetic features and applications in the space weather.…”
Section: Introductionmentioning
confidence: 99%